ASUHAN KEPERAWATAN PADA TN. U DENGAN HERNIA NUCLEUS PULPOSUS DI PANTI SOSIAL TRESNA WERDHA BUDI MULIA 1 KECAMATAN CIPAYUNG KOTA JAKARTA TIMUR - Gita Christin Ramadhani (2023)
Background : Hernia Nucleus Pulposus (HNP) is a protrusion of the nucleus pulposus that is pushed through a torn nucleus fibrosus caused by a degenerative process and repeated trauma. This research was conducted to analyze the application of nursing care to Mr. U with Hernia Nucleus Pulposus (HNP) includes nursing assessment, nursing diagnosis, nursing intervention, nursing implementation, and nursing evaluation. Research Methods : The design used is descriptive using the case study method. Research Results : Nursing problems that arise in cases are impaired physical mobility associated with decreased muscle strength. After carrying out nursing actions for 4 x 24 hours by providing active range of motion (ROM) exercises for 20 minutes a day the results of the nursing evaluation were resolved with the goals and criteria for the results set. Conclusion : Application of nursing care to Mr. U with Hernia Nucleus Pulposus achieved the expected results due to good cooperation between nurses and patients and other health teams.